Under the Hood of an EdTech Study in Kenya: Implementation challenges, successes, and lessons learnt - Büchel, Konstantin; Crossley, Colin; Cullen, Claire; Letsomo, Thato (EdTech Hub, 2023)
In the years following a global pandemic that left 1.6 billion learners out of school, the global learning crisis has grown more urgent. Governments worldwide have sought technology-enabled education platforms that can support higher quality, resilient education systems. One cheap and easy tool for delivering remote educational support is basic mobile phones, which represent a potentially cost-effective and remote platform for adapting a range of proven pedagogical methods. To do so successfully, programme delivery should consider three key factors that include (1) careful training on delivering pedagogical methods in a phone setting, (2) Appropriate monitoring systems to ensure weekly delivery fidelity and, (3) an appropriate data and/or delivery infrastructure to enable programme monitoring. If done successfully, mobile phone programmes can present education ministries with an efficient delivery option for quality education at a fraction of the cost of higher-tech solutions. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

EdTech Evidence From Covid-19 Response: A thematic review of primary research from Bangladesh, Ghana, Kenya, Pakistan and Sierra Leone - Nicolai, Susan; Jefferies, Kate; Stepanek Lockhart, Ashley (EdTech Hub, 2023)
To better understand the use of EdTech interventions as part of response to the Covid-19 pandemic, EdTech Hub commissioned ten small-scale research studies in five low- and middle-income countries: Bangladesh, Ghana, Kenya, Pakistan, and Sierra Leone. This paper includes insight into research methodologies across these studies, with particularly interesting findings on how EdTech effectiveness is being measured. A semi-structured thematic analysis further provides insights in relation to four main user groups of learners, girls, teachers, and parents and caregivers and points to a series of cross-cutting factors that are important for EdTech interventions in low-resource settings. An overarching takeaway centres on the fact that having technology in place is a small part of EdTech effectiveness, with wider teaching and learning ecosystems accompanying EdTech deserving more attention. Overall, the studies reveal a symbiotic relationship between people and technology, reinforcing that EdTech works best when users are involved across design, iteration, awareness building, and engagement. Keywords: EdTech, Covid-19, digital, education, learning, remote An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

EdTech to Support Out-of-School Children and Adolescents - Thinley, Sangay; Rui, Yang (EdTech Hub, 2023)
This Helpdesk report was created in response to a request from the World Bank Malawi Education Team for a curated list of resources on examples of EdTech interventions targeting out-of-school children and adolescents to inform an ASA (Advisory Services and Analytics) output. The ASA output will provide policy options to improve second-chance learning and foundational skills for out-of-school children (OOSC). To provide the World Bank Malawi team with adequate information on the above. This curated list begins with an introduction to the use of EdTech to support out-of-school children and youth, and then moves on to present examples of such interventions and programmes within Malawi, as well the wider African region and the rest of the world. This list is designed to serve as a resource for the team and does not make any direct recommendations on actions to be taken. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found